Georgy Gachev and his Method of Thinking: Changing man and the World - Bakhtikireeva, Uldanai M. (The New Research of Tuva, 2024)
The article is dedicated to analyzing the intellectual legacy of the Soviet scholar Georgy Dmitrievich Gachev — a remarkable literary critic, philosopher, and cultural theorist. He is known as the author of the concept of accelerated literary development, creator of national models of the world, and an explorer of the connections between the humanities and natural sciences. All Gachev’s scholarly and creative pursuits found their expression in his unconventional works, which his children characterize as a “life-philosophical diary”. The article discusses Gachev’s unique approach to interpreting the world around him, conveyed through a distinctive style of writing that defies the rigid conventions of academic discourse. It concludes that strictly hierarchical presentation of Gachev’s ideas is nearly impossible; therefore, the article relies on primary sources rather than interpretations or critiques of his work.